Determinant Factors of Academic Stress: A Study of First-Year University Students in Indonesia - Putra, Ade Herdian; Ardi, Zadrian (Jurnal Kajian Bimbingan dan Konseling, 2024)
Academic stress can reduce academic performance in first-year university students. Based on theoretical studies and previous research, three factors are predicted to influence academic stress: academic self-efficacy, life satisfaction, and happiness. This study analyzes the correlation of academic self-efficacy, life satisfaction, and happiness with first-year university students' academic stress. This research uses a quantitative approach with correlational methods and path analysis. The participants in this research were 720 first-year university students in Indonesia. The research instruments used were the Academic Self-Efficacy Scale, Life Satisfaction Scale, Happiness Scale, and Academic Stress Scale. Research data was collected online and then analyzed using the partial-least squares-structural equation model (PLS-SEM) technique. The results of this study show that life satisfaction and happiness are negatively and significantly correlated with first-year university students' academic stress. Furthermore, this research shows that happiness is the most determinant factor for academic stress, so it acts as a mediator in the correlation of academic self-efficacy and life satisfaction with first-year university students' academic stress. These three factors must be considered to reduce first-year university students' academic stress.